Synthesis of a New Homologous Series of 4-n-Alkoxy-2,3,5,6-tetramethyl-phenyl-4’-nitrobenzene - Hussein, F.H.; Al-Lami, E.S.; Al-Hamdany, R.E. (Asian Journal of Chemistry, 2010)
4-n-Alkoxy-2,3,5,6-tetramethylphenyl-4'-nitroazeibenzene where the number of carbon atoms in the alkoxy group varies from 2-8, were synthesised. The structures of the prepared liquid crystals were characterised on the basis of their UV-visible, IR spectral data and on their elemental analysis. Reversed phase high performance liquid chromatography analysis was used to check the degree of purity of the prepared liquid crystals.